Loan origination under soft- and hard-information lending - Roman Inderst (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2009)
This paper presents a novel model of the lending process that takes into account that loan officers must spend time and effort to originate new loans. Besides generating predictions on loan officers' compensation and its interaction with the loan review process, the model sheds light on why competition could lead to excessively low lending standards. We also show how more intense competition may fasten the adoption of credit scoring. More generally, hard-information lending techniques such as credit scoring allow to give loan officers high-powered incentives without compromising the integrity and quality of the loan approval process. The model is finally applied to study the implications of loan sales on the adopted lending process and lending standard.
urn:nbn:de:hebis:30-72998
Keywords: 330